The Epitope-Specific Anti-human CD4 Antibody MAX.16H5 and Its Role in Immune Tolerance - Stahl, Lilly; Duenkel, Anna; Hilger, Nadja; Tretbar, Uta Sandy; Fricke, Stephan (Frontiers in Immunology, 2019)
T cell modulation in the clinical background of autoimmune diseases or allogeneic cell and organ transplantations with concurrent preservation of their natural immunological functions (e.g. pathogen defense) is the major obstacle in immunology. An anti human CD4 antibody (MAX.16H5) was applied intravenously in clinical trials for the treatment of autoimmune diseases (e.g. rheumatoid arthritis) and acute late-onset rejection after transplantation of a renal allograft. The response rates were remarkable and no critical allergic problems or side effects were obtained. During the treatment of autoimmune diseases with the murine MAX.16H5 IgG1 antibody its effector mechanisms with effects on lymphocytes, cytokines, laboratory and clinical parameters, adverse effects as well as pharmacodynamics and kinetics were studied in detail. However, as the possibility of developing immune reactions against the murine IgG1 Fc-part remains, the murine antibody was chimerized, inheriting CD4 directed variable domains of the MAX.16H5 IgG1 connected to a human IgG4 backbone. Both antibodies were studied in vitro and in specific humanized mouse transplantation models in vivo with a new scope. By ex vivo incubation of an allogeneic immune cell transplant with MAX.16H5 a new therapy strategy has emerged for the first time enabling both the preservation of the graft versus leukemia (GVL) effect and the permanent suppression of the acute graft versus host disease (aGVHD) without conventional immunosuppression. In this review, we especially focus on experimental data and clinical trials obtained from the treatment of autoimmune diseases with the murine MAX.16H5 IgG1 antibody. Insights gained from these trials have paved the way to better understand the effects with the chimerized MAX.16H5 IgG4 as novel therapeutic approach in the context of GVHD prevention.